An Examination of the Key Drivers of Amendments to the Standard Forms of Contract in the South African Construction Industry - Mewomo, Modupe Cecilia; Aigbavboa, Clinton; Lesalane, Portia (Penerbit Universiti Sains Malaysia, 2018)
Some of the perceived benefts of standard forms of contract are standardisation, uniformity, stability and the availability of well-established terms and conditions which allow predictability and greater certainty in legal relations. Thus, the standard forms are widely adopted in the construction industry to facilitate the contractual arrangements between contracting parties in a construction project. Having become commonplace in construction transactions, they are often generally accepted by the various contracting parties and their advisers. Notwithstanding its importance, literature suggests that it is practically unfeasible to devise a standard form of contract that would cater for all eventualities and construction issues that might occur in construction projects. As a result, the existing standard forms are sometimes amended or modifed in order to ft the clients' requirements and also to suit the contractors' expectations. This paper therefore investigates the key factors that drive amendments to the standard forms of contract in the South African construction industry. Considering the fact that this paper presents fndings that relied on a descriptive survey method, the mean item score was used for presenting the results. The data was obtained through an online questionnaire survey sent to the construction professionals who are usually involved in the selection of contract forms for the client in the Gauteng Province of South Africa (SA). The data was analysed using the statistical package for the social sciences (SPSS) and the results indicate that "altering risk allocation", "inserting additional obligation" and "correcting something which is not applicable" are the three prominent factors that highly drive the amendment of standard forms of contract in the Gauteng Province of South Africa